In vitro antimicrobial activity of daptomycin alone and in adjunction with either amoxicillin, cefotaxime or rifampicin against the main pathogens responsible for bacterial meningitis in adults. (June 2021) - Maldiney, Thomas; Bonnot, Dorian; Anzala, Nelson; Albac, Sandrine; Labrousse, Delphine; Varon, Emmanuelle; Amoureux, Lucie; Chapuis, Angélique; Bador, Julien; Neuwirth, Catherine; Croisier, Delphine; Chavanet, Pascal
Highlights: No antagonism of daptomycin regarding the activity of cefotaxime against Neisseria meningitidis. Daptomycin improves β-lactam antimicrobial activity towards pneumococcus and Listeria. Reassuring evidence of the clinical potential of daptomycin adjunction in the treatment of bacterial meningitis. ABSTRACT: Objectives: As daptomycin adjunction is currently under clinical evaluation in the multicentre phase II AddaMAP study to improve the prognosis of pneumococcal meningitis, the present work aimed at evaluating the in vitro antimicrobial activity of daptomycin-based combinations against some of the most frequent species responsible for bacterial meningitis. Methods: Clinically relevant strains of Streptococcus pneumoniae, Listeria monocytogenes, Haemophilus influenzae and Neisseria meningitidis were obtained from National Reference Centers. The antimicrobial activity of amoxicillin, cefotaxime and rifampicin, either alone or in association with daptomycin, was explored through the determination of minimum inhibitory concentration (MIC) and fractional inhibitory concentration index (FICI) as well as time–kill assay (TKA) using the broth microdilution method. Results: All species taken together, the adjunction of daptomycin had no deleterious impact on the antimicrobial activity of amoxicillin, cefotaxime or rifampicin in vitro . Regarding Gram-positive bacteria, FICI and TKA analysis confirmed a global improvement of growth inhibition and bactericidal activity due to the adjunction of daptomycin. The synergistic effect prevailed for L. monocytogenes as demonstrated by FICI mainly <0.5 and a dynamic TKA-based synergy rate >50%. In addition, daptomycin-based associations did not modify the activity of β-lactam antibiotics or rifampicin against Gram-negative bacteria, notably N. meningitidis . Conclusion: These results bring comforting evidence towards the clinical potential of daptomycin adjunction in the treatment of bacterial meningitis, which supports the ongoing AddaMAP clinical trial.